2021
DOI: 10.3390/ma14030635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Steel Slag Aggregate on Pavement and Flame-Retardant Performance of Warm-Mixed Flame-Retardant Asphalt Concrete

Abstract: With the rapid development of tunnel construction, tunnel safety and the shortage of high-quality aggregates have concerned researchers so that this issue has become a research hot spot in the past few years. In the present study, we intended to prepare warm-mixed flame-retardant asphalt concrete using steel slag aggregate and evaluate its pavement and flame retardant performance. In this regard, the chemical composition and microstructure of the steel slag were studied using X-ray fluorescence analysis (XRF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
(12 reference statements)
2
8
0
Order By: Relevance
“…The added steel slag raises the ignition temperature and delays the ignition time of the asphalt mixture. 4 The optimal contents of magnesium hydroxide (MH), phosphorus, and decabromodiphenyl ethane in asphalt have been identified to decrease its flammability. The incorporation of these flame retardants has positive influences on the flammability of asphalt.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The added steel slag raises the ignition temperature and delays the ignition time of the asphalt mixture. 4 The optimal contents of magnesium hydroxide (MH), phosphorus, and decabromodiphenyl ethane in asphalt have been identified to decrease its flammability. The incorporation of these flame retardants has positive influences on the flammability of asphalt.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Numerous studies were conducted on steel slag which used in asphalt mixture, Ziaee et al selected Electric Arc Furnace Slag (EAFS) as coarse aggregates in Warm Mix Asphalt (WMA) mixtures, and their test results showed that EAFS can improve the mechanical properties of WMA mixtures [3]. Ren et al [4] proposed a method to characterize the combustion degree and evaluate the flame-retardant performance of the steel slag asphalt concrete, it was found that steel slag asphalt concrete has excellent flame-retardant performance and is a suitable choice for tunnel pavement. The proper content of steel slag would improve the indirect tensile strength [5], high-temperature performance [6], low-temperature fatigue life [7,8], and it is far from that.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the rapid development of the transportation industry, the traffic volume has been growing rapidly. The ratio of overloaded vehicles is large, which leads to serious ruts and other diseases at highway intersections and uphill sections, and seriously affects the comfort and safety of driving [ 1 , 2 , 3 , 4 ]. Qingchuan rock asphalt (QRA) is not only rich in reserves but also has the advantages of high nitrogen content, good durability, and good compatibility with base asphalt.…”
Section: Introductionmentioning
confidence: 99%